RANCANG BANGUN SISTEM RAPORT DIGITAL BERBASIS JAVA (D-RAPORT) DI SDN SUKATANI 03 DEPOK - Maulana Agung Saputro; . Khalidah (Universitas Teknokrat Indonesia, 2022)
Administration of academic activities at SDN Sukatani still uses a manual process. This can allow academic files to be lost, damaged and even a buildup of documents so that the search for documents for a number of students will be ineffective and inefficient. Therefore, there is a need for a system that can facilitate academic services. This study aims to design a Java-based Digital Report Card (d-Raport) system at SDN Sukatani 03 Depok. The method used in the design of the system is the waterfall method. The stages of this method, namely analysis, design, implementation, and testing. This system is built based on the desktop with the Java programming language. This system produces a student report card score module, a student attendance data module, a student savings data module, and a library book borrowing data module. This system is useful for SDN Sukatani in academic administration management.